Stock Market Volatility Dynamics around National Elections : Empirical Evidence from Asian Countries - Hong, Kon Wah (2015)
This paper investigates a sample of 8 Asian countries to test whether the stock market volatility would be induced higher during national election periods. Our empirical findings show the country-specific component of variance in election periods can easily reach up to 43% higher than the no election periods. It indicates that the investors are shocked with the election outcomes and investors’ sentiments are affected by the political events, no matter how well the preparation is made by investors. For further research on the magnitude of excessive volatility, the minority government can significantly enhance the degree of volatility while there is no political coalition hold more than half of the parliament seats. On the contrary, early election can reduce the level of volatility because early election can settle down the country-specific political strife and let the eligible voters choose the most suitable political coalition to manage the country. The investors who choose to invest in a country that is facing election event, the compensation for taking additional risk in the political event is negligible and the modest return may only suitable for those risk lover. Our results show the important implications for the index tracking fund and hedge fund managers that need to beware the volatility risk during political events.